Molecular identification of isolates of the Trichophyton mentagrophytes complex - Frías-De-León, María Guadalupe (Int J Med Sci, 2020)
Background: The Trichophyton mentagrophytes complex is the second most common causal agent of dermatophytosis. It comprises five species—T. mentagrophytes, T. interdigitale, T. erinacei, T quinckeanum, and T. benhamie, as well as nine different genotypes of T. mentagrophytes / T. interdigitale—which are morphologically similar; however, their susceptibility to antifungal agents may differ. For targeted therapy and better prognosis, it is important to identify these species at a molecular level. However, since many hospitals lack molecular methods, the actual aetiology of dermatophytosis caused by this complex remains unknown. Objective: To characterize 55 anthropophilic isolates of the T. mentagrophytes complex recovered from a dermatological centre in Yucatán, Mexico. Material and methods: Fifty-five isolates of the T. mentagrophytes complex were obtained from patients with tinea capitis, tinea pedis, tinea corporis, tinea barbae, and tinea unguium. They were characterized by their colonial and microscopic morphology on Sabouraud dextrose agar (SDA) and through the sequencing of a fragment from the region ITS1-5.8S-ITS2. Results: All colonies grown on SDA were white. Forty-six isolates formed colonies with a powdery texture, while nine isolates formed colonies with a velvety texture. The micromorphological features were typical of the T. mentagrophytes complex. The molecular analysis revealed that 55 isolates were microorganisms that belonged to the T. mentagrophytes complex, that 46 formed powdery colonies representing T. mentagrophytes, and that the other nine isolates that formed velvety colonies represented T. interdigitale. The latter nine isolates were obtained from patients with tinea pedis, tinea corporis, and tinea unguium. Conclusions: The colony morphology on SDA led to the identification of 46 isolates as T. mentagrophytes and nine isolates as T. interdigitale. At a molecular level, the species identified by their morphology were identified only as T. mentagrophytes complex.